Analisis Laporan Keuangan Masjid Berbasis ISAK No. 35 Tentang Penyajian Laporan Keuangan Entitas Berorientasi Nonlaba (Studi Kasus 5 Masjid di Kabupaten Simalungun) - Nirwana, Nirwana Afiah Hidayati; Hendra Harmain; Nurwani, Nurwani (Journal Research of Economic and Bussiness, 2025)
This research aims to determine the financial records of mosques in Simalungun Regency and implement the Interpretation of Financial Accounting Standards (ISAK) No. 35 concerning the presentation of financial reports of non-profit oriented entities. This research uses a descriptive qualitative approach method using primary data sources from direct sources or first parties, in this case mosque administrators, as well as secondary data, namely data in the form of books, notes and other documents related to the research object. The data collection techniques used in this research are observation, interviews and documentation techniques. Based on the results of data analysis, research results showed that the recording of the financial reports of the five mosques was not in accordance with ISAK No. 35 due to the management's limited knowledge of accounting and financial reporting. Therefore must creates an accounting cycle for the financial data obtained from the five mosques using financial data for July 2020, starting from the general journal to the financial report in accordance with ISAK No. 35, which includes the Financial Position Report, Comprehensive Income Report, Report on Changes in Net Assets, Cash Flow Statements, and Notes to Financial Statements. It is hoped that this will be able to assist mosque administrators in recording financial reports in the following period to improve the quality of financial reports so that they comply with ISAK No. 35. Keyword: ISAK No. 35, Non-profit Oriented Entity, Financial Statements